Difference in shade tolerance drives the mixture effect on oak productivity. (26th June 2017) - Toïgo, Maude; Perot, Thomas; Courbaud, Benoit; Castagneyrol, Bastien; Gégout, Jean‐Claude; Longuetaud, Fleur; Jactel, Hervé; Vallet, Patrick
Abstract: Assessing how species productivity in mixtures is influenced by species shade tolerance (ST) and phylogeny would be helpful to improve our general understanding of the relationship between tree species diversity and productivity in forests. We investigated the effects of differences in ST and phylogenetic distances (PDs) between pairs of species on the productivity of Quercus petraea growing in 18 mixtures in lowland temperate forests. We calculated the mixture effect as the difference in productivity of Q. petraea in mixed vs. pure stands. Our analyses were based on data from seven annual campaigns of the French National Forest Inventory covering 1, 573 plots. The mixture effect on Q. petraea productivity increased when the ST of the companion species decreased. Compared to its productivity in pure stands, Q. petraea productivity in mixed coniferous stands varied from −14.6% up to +39.6% as the ST of the companion species inversely varied from highest to lowest. With broadleaved companion species, the mixture effect varied from −10% up to +13.9% with decreasing ST. We found no effect of PD between Q. petraea and the companion species on the mixture effect. Synthesis . Our results confirm that shade tolerance is an important driver of the diversity effect on productivity at species level in temperate forests and that phylogenetic distance is not a relevant proxy for species functional dissimilarity. Abstract : The mixture effect on Quercus petraea productivity increased when the shade tolerance of the companion species decreased. Our results confirm that shade tolerance is an important driver of the diversity effect on productivity at species level in temperate forests and that phylogenetic distance is not a relevant proxy for species functional dissimilarity.